Cryosurgical and cryoradiation treatments in patients with calvarial skin cancer - I. N. Pustynskiy; S. I. Tkachev; T. D. Tabolinovskaya; S. B. Alieva (Опухоли головы и шеи)
The authors developed a novel cryoradiation treatment in patients with locally advanced basal cell and squamous cell carcinoma of the head skin, which included a combination of tumor cryogenic and radiation exposures. of a tumor. Immediately before each radiotherapy session, local tumor cooling is carried out until the freezing temperature is achieved at the tumor-intact tissue border. Irradiation is performed in cycles: at a single daily focal dose of 2.0–2.5 Gy during 5 days at a 2-day interval until the cumulative focal dose of 60–70 Gy is achieved. The results of cryosurgical and cryoradiation treatments were investigated in 112 patients with basal cell (n = 101) and squamous cell (n = 11) carcinoma of the calvarial skin. Among the patients, there were 48 (42.9 %) men and 64 (57.1 %) women; their mean age was 67.1 (39–107) years. The skin tumor was located in the parietal region in 30 (26.8 %) patients, in the temporal region in 55 (49.1 %), in the frontal region in 26 (23.2 %), and in occipital region in 1. The size of the neoplasms in all the patients was more than 1 cm; the tumors belonged to a high recurrence risk group. The method of treatment was chosen according to indicators. The postoperative follow-ups of the patients were 2 to 14 years (median follow-up, 7 years). Recurrences of skin cancer were diagnosed in 5 (4.5 %) of the 18 patients: 1 (1 %) after treatment for its primary forms and 4 (22.2 %) after that of recurrences. Cryosurgical and cryoradiation treatments performed as clinically indicated could yield good functional, aesthetic, and long-term results and ensure effective rehabilitation in patients after the treatment conducted.